2021
DOI: 10.1002/lol2.10232
|View full text |Cite
|
Sign up to set email alerts
|

Risk to native marine macroalgae from land‐use and climate change‐related modifications to groundwater discharge in Hawaiʻi

Abstract: Coastal groundwater-dependent ecosystems and associated species, including native macroalgae, are highly adapted to the lowered salinity and nutrient subsidies of natural flows of submarine groundwater discharge (SGD). However, with climate and land-use change-induced shifts in SGD, invasive macroalgae are outcompeting native species, with drastic implications for these important ecosystems. This article contributes to a synthetic understanding of these processes by providing a salient case study from Oʻahu, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…While Dailer et al (2010) found elevated δ 15 N (> 50‰) in areas adjacent to wastewater treatment plants around Maui, our δ 15 N values reflected possible fertilizer use with high %N. This variability in potential source may be due to the spatial and possible temporal heterogeneity of SGD sources (Dailer et al 2012b) depending on spring location, proximity to point and nonpoint sources of nutrient pollution, as well local currents and water motion (Amato et al 2016; Dulai et al 2021). A previous study from coastal waters of O‘ahu near a stormwater outflow in a highly populated development that included cesspools and/or septic systems found δ 15 N and %N values of 15.1‰ and 3.5%, respectively (Lapointe and Bedford 2011).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…While Dailer et al (2010) found elevated δ 15 N (> 50‰) in areas adjacent to wastewater treatment plants around Maui, our δ 15 N values reflected possible fertilizer use with high %N. This variability in potential source may be due to the spatial and possible temporal heterogeneity of SGD sources (Dailer et al 2012b) depending on spring location, proximity to point and nonpoint sources of nutrient pollution, as well local currents and water motion (Amato et al 2016; Dulai et al 2021). A previous study from coastal waters of O‘ahu near a stormwater outflow in a highly populated development that included cesspools and/or septic systems found δ 15 N and %N values of 15.1‰ and 3.5%, respectively (Lapointe and Bedford 2011).…”
Section: Discussionmentioning
confidence: 70%
“…Knowledge of the nutrient regimes from shallow to mesophotic reefs throughout the Hawaiian Archipelago, informed by known land‐use practices and their recent changes, could be used to identify areas that are likely to be influenced by point and nonpoint pollution around the Main Hawaiian Islands via increased nitrogen loading in macroalgal tissue (Lapointe and Bedford 2011; Dailer et al 2012a,b; Amato et al 2016). SGD clearly plays a role in supplying enhanced nutrient loads to shallow‐water depths around the Main Hawaiian Islands (Dailer et al 2012a,b; Amato et al 2018; Dulai et al 2021), and may also fuel the growth of mesophotic invasive or bloom‐forming macroalgae in volcanic islands via submarine vents (Attias et al 2020, 2021). Conversely, upwelling or internal waves from deeper water (200 to 350+ m depths) may introduce nitrogen inputs with altered nitrate δ 15 N in the range of 6–7‰ (Casciotti et al 2008; Knapp et al 2011; Wilson et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…However, coastal ecosystems also face severe salinization due mainly to a combination of water withdrawal—for irrigation and human consumption—and sea‐level rise (Oude Essink et al 2010; Mahmuduzzaman et al 2014; Dasgupta et al 2015; Mabrouk et al 2018). To elucidate problems facing sensitive groundwater dependent coastal ecosystems in the Pacific and beyond, Dulai et al (2021) use Hawaii as a case study to show how changes in groundwater nutrient and salinity discharge levels modify native marine macroalgal growth rates, branching patterns, and ostensibly weaken ensuing competitive interactions with invasive macroalgae.…”
Section: State Of the Sciencementioning
confidence: 99%
“…Nutrients are expected to be higher in SGD relative to oligotrophic seawater, such as coral reefs, due to higher concentrations of nitrogen in rainwater (~ 1 µmol L -1 N+N in Mo'orea 42 ), downward leaching of N and P from terrestrial matter and/or dissolution of seabird guano [43][44][45] , and high SiO3 2-and PO4 3values from mineral weathering 46,47 . Natural SGD is an important source of new nutrients to coral reefs 25,29 and can benefit native algae and corals 32,48 . However, the highly elevated values at our sites (e.g., up to ~ 280 µmol L -1 of N+N at Varari; Table 1) may be a result of septic drainage, fertilizer from nearby agriculture, and other anthropogenic activities contaminating the groundwater 42 .…”
Section: Fundamental Differences In Groundwater Discharge Chemistry I...mentioning
confidence: 99%